TIKTOK-BASED VIDEO TUTORIAL LEARNING MEDIA ON THE TOPIC OF SIMPLE 3D DRAWING WITH CAD - Zadi, Fikran Fauzul; Hamdani, R. Aam (Universitas Pendidikan Indonesia, 2024)
This research aims to produce a product in the form of a TikTok-based video tutorial learning media on the topic of basic 3D drawing command functions with CAD, and to determine the feasibility and user response towards this media. The research employs the Design Based Research (DBR) development model, which consists of four stages: problem identification, prototype solution development, testing and solution improvement, and reflection and solution implementation. The testing was conducted in class XI- DGM 1 in the subject of designing techniques with CAM, with a sample size of 35 students. The instrument used was a questionnaire. The research yields a video tutorial learning media based on the TikTok application for basic 3D drawing command functions with CAD. The feasibility assessment conducted by 3 subject-matter experts and 3 media experts indicates that the developed TikTok-based video tutorial learning media is deemed